Strategic Placement of Solar Power Plant and Interline Power Flow Controllers for Prevention of Blackouts - Akanksha Mishra; Nagesh Kumar Gundavarapu Venkata; Sravana Kumar Bali; Venkateswara Rao Bathina; Uma Maheswari Ramisetty; Srikanth Gollapudi; Hady Habib Fayek; Eugen Rusu (Inventions, 2022)
In these post COVID times, the world is going through a massive restructuring which India can use to its benefit by attracting foreign industrial investment. The major requirement is a reliable and ecofriendly electrical power source. Of late, renewable energy sources have increasingly become popular as alternative source of electricity. They can provide immense aid in improving the reliability of the power system, when placed properly. The alternative integrated energy sources along with FACTS devices can provide a promising future for reliable power systems. In this paper, an effective location for the solar power unit and Interline Power Flow Controller using Line Severity Index is proposed in order to avoid contingencies. An Indian 62 bus system and IEEE 57 bus system are considered for the study. The Firefly algorithm is used to tune the IPFC in the Integrated Energy Systems scenario, for a dual objective function. The effect of placement of the solar unit and the optimized IPFC is analyzed and studied in detail in this paper.